The behavioural and molecular characterisation of a novel LRRK2 BAC transgenic rat model of Parkinson’s disease - Sloan, M; Maximilian Sloan (2014)
Mutations in the leucine-rich repeat kinase II (LRRK2) gene cause autosomal-dominant Parkinson’s disease (PD) which is indistinguishable from sporadic forms of the disease. However, the mechanism by which LRRK2 mutation promotes PD pathology and the functions of the LRRK2 protein itself are currently unknown. Transgenic animal models, expressing PD-linked genes, have been crucial in developing a clearer picture of the mechanisms behind PD progression. Bacterial artificial chromosome (BAC) transgenics, in particular, allow for physiologically relevant disease models to be generated, encompassing entire gene sequences and using endogenous promoters, which result in an accurate recapitulation of spatiotemporal gene expression. We have, therefore, developed BAC transgenic rats expressing human LRRK2. These lines express either human wild-type, G2019S mutant (the most common LRRK2 mutation) or R1441C mutant (the LRRK2 mutation leading to a more aggressive pathology) LRRK2. These rats display LRRK2 transgene expression patterns in the brain which highly resemble human LRRK2 expression. We subsequently aged these lines for the purposes of behavioural and molecular analysis. Additionally, we have performed a number of in vitro studies in neurons cultured from these rats to further investigate the effects of pathological forms of LRRK2. Mutant LRRK2 transgenic rats displayed progressively impaired striatal dopaminergic release along with corresponding behavioural deficits, both motor and cognitive. These motor deficits could be rescued by treatment with levodopa, implying a similar underlying pathological process to PD. These phenotypes occurred in the absence of any overt degeneration of the dopaminergic neurons of the substantia nigra pars compacta or other PD-associated neuropathological markers. We also detected a number of molecular alterations associated with mutant LRRK2 expression including altered LRRK2 phosphorylation and in vitro evidence of altered autophagic processes. In conclusion, these rats recapitulate a number of the key features of Parkinson’s disease and provide clues as to the progression of pathology in PD.